If Formula1" title="\mathrm {y = (x + \sqrt{1+x^{2}})^{m}}" alt="\mathrm {y = (x + \sqrt{1+x^{2}})^{m}}" align="absmiddle" class="latex-formula">, then prove that
.
Note : y₁ and y₂ refer to the first and second derivatives.
1 answer:
Answer:
See below for proof.
Step-by-step explanation:
<u>Given</u>:
<u>First derivative</u>
<u />
<u />
<u />
<u>Second derivative</u>
<u />
<u>Proof</u>
You might be interested in
Big sundi and more bigger with spice
Answer:
Concept: Graph Analysis
Horizontal Asy: 1 Vertical Asy: 4 Domain: -inf to inf U -inft to inf X intercept: 7 Y intercept: 2 End behavior: Continous to real numbers, hence negative and positive infinity Give brainlist
Answer:
Solution given:
r=3km
area of sector bounded by a 90° arc=90°/360°*πr²
=¼*π*3²
=<u>9/4 π or 7.068km²</u>
is a required answer
Answer:
Try taking a screen shot as this is indecipherable.
Step-by-step explanation:
Answer:
41=79 41 is equal to 79.